Occurrence of aflatoxin M1 and its main determinants in raw cow milk the Chiriquí in Panama farms - Vega, Aracelly; Costamagna, Dianela A.; Signorini, Marcelo L.; Melgar M., Audino; Villarreal, Eduard A. (Archivos Latinoamericanos de Nutrición (ALAN), 2025)
Introduction: Aflatoxin contamination and its effects on human health have been a global concern and a research subject in developed countries for many decades. However, data generated from Latin America are scarce. Objective. To evaluate the occurrence of aflatoxin M1 (AFM1) and to identify its determinants in raw cow milk under current farm feeding practices in Panama. Materials and Methods. The study included 32 raw milk samples and 79 dairy cattle feed samples from 32 farms suppliers for a Panama dairy processing company. Contents of aflatoxin B1 (AFB1) and AFM1 were determined using HPLC-FLC and immunoaffinity columns. The carry-over of AFB1 to AFM1 was determined according to aflatoxin contents in feed and raw milk. A survey was also applied to all dairy farmers in the study regarding the explanatory variables associated with AFM1 occurrence in milk. Results. The overall prevalence of AFB1 in feeds was 39.2%, whereas the highest prevalence was for concentrate feed (74.3%) and the lowest (3.70%) for fresh forages. The occurrence of AFM1 in milk was 46.8%. The carry-over from AFB1 to AFM1 averaged 2.36%, which is characteristic of low-producing cows. Conclusion. The incidence and concentration of AFB1 in dairy cattle feed observed in the present study resulted under the maximum levels set by the U.S. Food and Drug Administration (FDA) and the European Union Commission Regulation (EC). Under current feeding practices, silage and haylage fed are determinants of AFM1 occurrence in tropical raw cow milk. Introducción: La contaminación por aflatoxinas y sus efectos en la salud humana ha sido de preocupación global y un tema de investigación en los países desarrollados durante muchas décadas, pero los datos generados desde América Latina son escasos. Objetivo. Evaluar la presencia de aflatoxina M1 (AFM1) e identificar sus determinantes en la leche cruda de vaca bajo prácticas actuales de alimentación en Panamá. Materiales y métodos. El estudio incluyó 32 muestras de leche cruda y 79 muestras de alimento para ganado lechero de 32 fincas proveedoras de una empresa procesadora de lácteos en Panamá. Los contenidos de aflatoxina B1 (AFB1) y AFM1 se determinaron utilizando HPLC-FLC y columnas de inmunoafinidad. Se calculó la tasa de transferencia de AFB1 a AFM1 de acuerdo a los contenidos de aflatoxina en el alimento y la leche cruda. También se aplicó una encuesta a todos los productores lecheros participantes en el estudio, sobre las variables explicativas asociadas con la ocurrencia de AFM1 en la leche. Resultados. La prevalencia total de AFB1 en los alimentos fue del 39,2%; la prevalencia más alta fue para los concentrados (74,3%) y la más baja (3,70%) para los forrajes frescos. La aparición de AFM1 en la leche fue del 46,8%. La tasa de transferencia de AFB1 a AFM1 promedió 2,36%, característico en vacas de baja producción. Conclusiones. La presencia y concentración de AFB1 en el alimento para ganado lechero observada en el presente estudio resultó por debajo de los niveles máximos establecidos por las regulaciones de la Administración de Alimentos y Medicamentos de los Estados Unidos (FDA) y la Comisión de la Unión Europea (EC). Según las prácticas de alimentación actuales, el tipo de ensilaje y el henolaje suministrado son determinantes de la ocurrencia de AFM1 en la leche cruda de vaca en el trópico